Development and validation of a cognitive skills questionnaire for adolescent offenders: The Cognitive Skills Questionnaire for Youth (CSQ-Y) - Alba Robles, José Luis; Medrano, José G; Montañéz Alvarado, Priscila; López Latorre, María J; Cuervo García, Ana L. (Anuario de Psicología Jurídica, 2026)
The present study aimed at psychometrically validating the Cuestionario de Habilidades Cognitivas in Ciudad Juárez, Chihuahua, Mexico. A sample of 502 adolescents aged 15 to 17 years from Bachilleres # 19 high school in Ciudad Juárez participated in the study. The questionnaire was refined to 20 items based on expert judgment, followed by a pilot application. Exploratory factor analysis revealed the instrument’s structure consisting of three factors, with acceptable convergent and discriminant validity. Invariance analysis resulted in no significant differences across samples, while confirmatory factor analysis yielded a reliability coefficient alpha of .73. The Kaiser-Meyer-Olkin measure was .72, and Bartlett’s significance test with a chi-square value of 947.543 (df = 190, p < .000) explained 69% of the total variance. The model fit indices were satisfactory with a chi-square of 96.89, GFI of .94, CFI of .95, and RMSEA of .04. The study sought to identify prevalent cognitive conditions and issues among adolescents to facilitate the development of interventions and psychoeducational treatments for violence-related behavioral problems. The efficacy of the CHC questionnaire was substantiated, along with its utility in identifying cognitive scenarios in adolescents.
La elaboración y validación de un Cuestionario de Habilidades Cognitivas para Adolescentes Infractores: el Cuestionario de Habilidades Cognitivas para Jóvenes (CHC)
El presente estudio tuvo como objetivo validar psicométricamente el Cuestionario de Habilidades Cognitivas en Ciudad Juárez, Chihuahua, México. Participó una muestra de 502 adolescentes de entre 15 y 17 años del Bachilleres n.º 19 de Ciudad Juárez. El cuestionario fue depurado hasta quedar en 20 ítems, tras un juicio de expertos y una aplicación piloto. El análisis factorial exploratorio mostró una estructura compuesta por tres factores, con una validez convergente y discriminante aceptables. El análisis de invarianza no mostró diferencias significativas entre las muestras, mientras que el análisis factorial confirmatorio arrojó un coeficiente alfa de fiabilidad de .73. La medida de Kaiser-Meyer-Olkin fue de .72 y la prueba de significación de Bartlett obtuvo un valor de chi-cuadrado de 947.543 (gl = 190, p < .000), explicando el 69 % de la varianza total. Los índices de ajuste del modelo fueron satisfactorios, con un chi-cuadrado de 96.89, un GFI de .94, un CFI de .95 y un RMSEA de .04. El estudio pretendía indagar en las condiciones y los indicadores cognitivos frecuentes en adolescentes para facilitar el desarrollo de intervenciones y tratamientos psicoeducativos ante problemas de conducta relacionados con la violencia. La investigación confirmó la eficacia del cuestionario CHC y su utilidad para identificar escenarios cognitivos en población adolescente.
Keywords: cognition; social competences; Cognitive Skills Questionnaire for Youth (CSQ-Y); validation; habilidades cognitivas; competencias sociales; Cuestionario de Habilidades Cognitivas para Jóvenes (CHC); validación